Measurement of the Social Investment Impact of the Pertamina Sahabat Nelayan Program Using the Social Return on Investment Method (SROI) - Luthfi Nurwafi F.; Aryo Aji Asmoro; Milasania Shintadewi (Global Writing Academica Researching and Publishing, 2023)
To be able to improve the welfare of fishermen, Pertamina runs the Pertamina Sahabat Nelayan program. In this program, there is a Social Return on Investment (SROI) which helps reduce inequality and environmental degradation and increase welfare by combining social, environmental, and economic costs and benefits. This research then aims to see the SROI of the Pertamina Sahabat Nelayan program. This research will be conducted by measuring the existing impact using the SROI method. Meanwhile, the data obtained will be analyzed descriptively. The results of this study then found that this community empowerment program had an SROI value of 1.83. This means that the Pertamina Sahabat Nelayan program positively impacts the economy, society and environment. But unfortunately, this program has a negative impact, namely the existence of a group dependency on the role of PT Pertamina Patra Niaga Integrated Terminal Semarang in terms of communication with other parties and promotion of the program.